2013
DOI: 10.1371/journal.pone.0056037
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Phosphofructokinase Activity in Mycobacterium tuberculosis Reveals That a Functional Glycolytic Carbon Flow Is Necessary to Limit the Accumulation of Toxic Metabolic Intermediates under Hypoxia

Abstract: Metabolic versatility has been increasingly recognized as a major virulence mechanism that enables Mycobacterium tuberculosis to persist in many microenvironments encountered in its host. Glucose is one of the most abundant carbon sources that is exploited by many pathogenic bacteria in the human host. M. tuberculosis has an intact glycolytic pathway that is highly conserved in all clinical isolates sequenced to date suggesting that glucose may represent a non-negligible source of carbon and energy for this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 43 publications
2
56
0
Order By: Relevance
“…Previous studies with a phosphofructokinase A knock-out strain of Mtb showed glucose toxicity under hypoxic but not aerobic conditions (15). The difference in phenotype may arise from the position of the two enzymes in the glycolytic pathway.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies with a phosphofructokinase A knock-out strain of Mtb showed glucose toxicity under hypoxic but not aerobic conditions (15). The difference in phenotype may arise from the position of the two enzymes in the glycolytic pathway.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies with the adenosine triphosphate (ATP) synthase inhibitor, Bedaquiline, showed a delayed cidal effect when Mtb was grown on fermentable carbon sources (13), suggesting that Mtb can produce ATP through substrate level phosphorylation when oxidative-phosphorylation is limited. However, studies in mice with Mtb strains containing knockouts of glycolytic enzymes did not result in strong attenuation, thus leaving the role of glucose metabolism in the virulence and physiology of Mtb unclear (14,15).…”
mentioning
confidence: 99%
“…Furthermore, it has been reported that DosR antigens, including Rv2029c, induce predominant mono-and bifunctional (IFN-␥ and/or TNF-␣) CD4 ϩ and/or CD8 ϩ T cell responses in LTBI (33). Rv2029c (pfkB), a probable phosphofructokinase, is a key enzyme in glycolysis (58). A recent study suggests that, in M. tuberculosis, glycolysis leads to the accumulation of toxic metabolites, limiting M. tuberculosis survival under hypoxic conditions (58).…”
Section: Fig 4 Memory Phenotypes Of Monofunctional Ifn-␥mentioning
confidence: 99%
“…Rv2029c (pfkB), a probable phosphofructokinase, is a key enzyme in glycolysis (58). A recent study suggests that, in M. tuberculosis, glycolysis leads to the accumulation of toxic metabolites, limiting M. tuberculosis survival under hypoxic conditions (58). Rv1737c ϩ and TNF-␣ ϩ CD8 ϩ T cells in ltLTBI and PTB.…”
Section: Fig 4 Memory Phenotypes Of Monofunctional Ifn-␥mentioning
confidence: 99%
“…Additionally, glycolysis under hypoxic conditions leads to the accumulation of toxic byproducts (65). Therefore, fatty acids are considered to be a major carbon source of M. tuberculosis in vivo.…”
Section: Hierarchical Clusteringmentioning
confidence: 99%